Subconjunctival Emphysema After Descemet's Stripping Automated Endothelial Keratoplasty (DSAEK) - Ide, Takeshi (Bentham Open, 2008)
DSAEK has recently evolved as a preferred method in place of PKP. After DSAEK, we experienced subconjunctival emphysema, decreased air bubble in the AC and low IOP. This could lead to complications, higher rate of dislocation or infection. We should control the wound closure with suture when in doubt.